Pengembangan Buku Siswa Membaca Menulis Permulaan Berbasis Budaya Dengna Menggunakan Prosedur ADDIE Untuk Kelas 1 SD - Rahmawati, Magdalena Chori; Samino, Francine Avantie; Agustian, Murniati; Revaria, Noviria Retno; Ernestya, Teresa Gita (Jurnal PGSD, 2021)
The development research aims to produce a book for students to start reading and writing based on the Mentawai culture. The development of student book products refers to the ADDIE development mode. The results of the development research show the student books are categorized verry well from the aspect of material content, material accuracy, linguistics with the accumulation of the validity score range wich is 92%, while the student book design is categorized as verry good from aspects of book size, book cover design, book content design, book content illustrations with an accumulation of the validity score range of 94,26%. This shows that student book can be used in learning activities. The results of the analysis obtained criteria 81%-100%, then the qualified student’s book was verry good for use in learning. The culture-based reading and writing students’ book that was developed is said to be suitable for use learning activities.